Social Gathering Cards Learning Method to Enhance Students’ Critical Thinking Ability and Learning Outcomes - Maulana, Moh (Unversitas Negeri Malang, 2018)
This research was conducted in order to implement Social Gathering Card Learning Method and its impact on students’ critical thinking skills and student learning outcomes on economic subjects. This study applied a classroom action research in economics class in SMAN 6 Malang. The research was conducted in two cycles consisting of two meetings of each. The findings of the study showed that the application of social gathering card has increased during cycles for both students’ critical thinking skills and learning outcomes. In more detail, in the beginning, it was about 73.7 percent for students’ critical thinking skills and rose to the level of 89.4 percent in the end of period. Furthermore, the students’ cognitive abilities in the pretest were about 6.89 per cent with average score 55 and it rocketed to the level about 93.1 percent with the score about 77. In the other hand, in the second cycle, the pre-test score was about 23.7 percent with the average score 57 and the post-test score was about 96.5 percent with the average score about 80.Keywords: Social Gathering Card, Thinking Critically, Learning Outcomes